Problemas para a atividade internacional das unidades subnacionais: estados e municípios brasileiros - Vigevani, Tullo [UNESP] (Associação Nacional de Pós-Graduação e Pesquisa em Ciências Sociais - ANPOCS, 2006)
Both academic journals and actual experience suggest that the regional and international participation of sub-national governments is gaining force and importance, and may be raised as a significant issue for various countries. Internationally sub-national governmental participation has been growing for some time. The Brazilian example does not differ from this general pattern. The debate has not yet consolidated, and this question will be of major future importance. The attributes granted to federal states and municipalities in the Brazilian Constitution of 1988 open perspectives which can further the debate on the possibilities and effectiveness of decentralized international activities. The specialized literature of the 1990s enlarged the paradiplomatic concept and indicated the participation of governmental organizations, aside from national states in international action. This intertwined with the classical debates regarding national sovereignty and federalism. The challenge facing Brazil is to connect potential interests of external relations of state governments and municipalities with those of the national State.

Tant la littérature académique que l’expérience actuelle suggèrent que la participation régionale et internationale des gouvernements sous-nationaux gagne de la force et de l’importance et peut être considérée comme une question importante pour plusieurs pays. La participation internationale des gouvernements sous-nationaux s’accroît depuis quelques temps. L’exemple du Brésil n’est pas différent. Le débat n’est pas encore consolidé et cette question sera importante dans l’avenir. Les attributions des États et des municipalités ouvrent, selon la Constitution de 1988, des perspectives qui renforceront le débat sur la possibilité et l’effectivité d’actions internationales décentralisées. La littérature spécialisée des années 1990 a élargi le concept de paradiplomatie et a suggéré la participation, dans les actions internationales, d’organisations gouvernementales en dehors de l’État national. Le défi pour le Brésil est de conjuguer l’intérêt potentiel des gouvernements sous-nationaux et municipaux pour les relations internationales avec les intérêts de l’État national.

Tanto a literatura acadêmica como a experiência atual sugerem que a participação regional e internacional dos governos subnacionais está ganhando força e importância e pode ser considerada um fator importante para inúmeros países. No Brasil, debate sobre esse tema ainda não foi consolidado, mais certamente terá importância no futuro. As atribuições de estados e municípios estabelecidas pela Constituição de 1988 abrem perspectivas que fortalecerão a discussão sobre a possibilidade e a efetividade de ações internacionais descentralizadas. A literatura especializada dos anos de 1990 ampliou o conceito de paradiplomacia e sugeriu a participação de organizações governamentais, além do Estado nacional, em ações internacionais, o que se vincula ao debate clássico relativo à soberania nacional e ao federalismo. O desafio para o Brasil é como conjugar o potencial interesse pelas relações externas dos governos estaduais e municipais com os interesses do Estado nacional.
Problems for international action of sub-national governments: Brazilian states and municipalities
Problèmes à l'action internationale des gouvernements sous-nationaux: états et municipalités Brésiliennes
Keywords: Sub-national governments; Paradiplomacy; Brazilian foreign policy; International relations theory; Governos subnacionais; Paradiplomacia; Política externa do Brasil; Teoria das relações internacionais